Surface Free Energy Utilization to Evaluate Wettability of Hydrocolloid Suspension on Different Vegetable Epicarps - Osorio-Lira, F; Zamorano-Riquelme, M; Silva-Weiss, A; Silva-Vera, W; Gimenez-Castillo, B; Lopez-Polo, J (Multidisciplinary Digital Publishing Institute (MDPI), 2018)
Surface free energy is an essential physicochemical property of a solid and it greatly influences the interactions between vegetable epicarps and coating suspensions. Wettability is the property of a solid surface to reduce the surface tension of a liquid in contact with it such that it spreads over the surface and wets it, resulting from intermolecular interactions when the two are brought together. The degree of wetting (wettability) is determined by an energy balance between adhesive and cohesive work. The spreading coefficient (Scf/food) is the difference between the work of adhesion and the work of cohesion. Surface wettability is measured by the contact angle, which is formed when a droplet of a liquid is placed on a surface. The objective of this work was to determine the effect of hydroxypropyl methylcellulose (HPMC), κ-carrageenan, glycerol, and cellulose nanofiber (CNF) concentrations on the wettability of edible coatings on banana and eggplant epicarps. Coating suspension wettability on both epicarps were evaluated by contact angle measurements. For the (Scf/food) values obtained, it can be concluded that the surfaces were partially wet by the suspensions. Scf/food on banana surface was influenced mainly by κ-carrageenan concentration, HPMC-glycerol, κ-carrageenan-CNF, and glycerol-CNF interactions. Thus, increasing κ-carrageenan concentrations within the working range led to a 17.7% decrease in Scf/banana values. Furthermore, a HPMC concentration of 3 g/100 g produced a 10.4% increase of the Scf/banana values. Finally, Scf/fruit values for banana epicarps were higher (~10%) than those obtained for eggplant epicarp, indicating that suspensions wetted more the banana than the eggplant surface. © 2018 by the authors.